Pengaruh Promosi dan Kualitas Produk terhadap Keputusan Pembelian Konsumen di Perusahaan CV Kiral - Shinta Nurjanah; Erna Pujihartanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The garment industry in Indonesia has experienced rapid growth in line with the increasing demand for fashion products, particularly in Bandung Regency, which is one of the main garment centers. CV Kiral, as a garment company, faces intense competition, especially in terms of promotion and product quality, which are crucial factors in attracting consumers. This study aims to examine the influence of promotion and product quality on consumer purchasing decisions at CV Kiral, both partially and simultaneously. The research method employed is quantitative with a descriptive and verificative approach. The sample consisted of 100 respondents, who were CV Kiral consumers, determined using Cochran’s formula and selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression, t-test, F-test, and coefficient of determination with the assistance of SPSS software. The results indicate that promotion has a positive and significant effect on purchasing decisions, as does product quality, which also demonstrates a positive and significant influence. Simultaneously, promotion and product quality make a strong contribution to improving consumer purchasing decisions. Thus, the success of CV Kiral in facing competition is highly determined by the effectiveness of creative digital promotions and the consistency of product quality that meets consumer expectations.